The Legal Protection of Agricultural Land Sustainable Food in Mining Coal Area of East Kalimantan - Haris Retno Susmiyati; Rahmawati Al-Hidayah (Faculty of Law, Pattimura University, 2020)
The effort of fulfillment over people's food is a constitutional obligation of the State. The development of an increasingly large population can threaten the existence of the tropical wet forest area when opening the land needs of food became imperative. As was the case in East Kalimantan, the area of food land is diminishing because over the function of the land are massive for coal mining and palm oil plantations. This will bring up the feared conditions insistence to open forest areas to agricultural land of food. The Central Government has the authority to make the national policy while the local government is based on the provisions of Division of the authority of Government, have the authority to make policies related to land protection food crop sector ongoing in the area. This article would like to know (1) How is the legal content in the regulation regarding the protection of sustainable food crop lands at the national level; and (2) how is regional can make a regulation of the protection sustainable food crop lands. The method is used the legal research of normative, as well as by the method of analysis is analytic descriptive. Based on the results of the study it was concluded that the regulation of sustainable food crops land protection at the national level has been set in full, but the content of legal protection, there is a weakness in political designation, which allows agricultural lands sustainable food converted as long as there is not determination as a sustainable agricultural lands. In other words, the provision in The Law No 41 Of 2009 On The Protection Of Land For Sustainable Food Plantation, but in substance precisely open up opportunities for the occurrence over the function of the land. there is a regulation on the region level regarding legal protection one of them the Regional Regulation No 1 Of 2013 On The Protection Of Sustainable Agricultural Lands, but contain elements of weakness that requires a determination of the agricultural lands before protection While official functionary who is not determination agricultural location does not get strict sanctions. This is a weakness for the agricultural land which has not been established, although physically it is the agricultural land of food, but because there is no designation then will not be affordable by the regulation of the area.